Influencer marketing on Instagram—The optimal disclosure strategy from influencers' and marketers' perspectives - Zofia Saternus; Cristina Mihale-Wilson; Oliver Hinz (Electronic Markets, 2024)
This article explores the impact of different advertising disclosure strategies (i.e., explicit sponsorship disclosure, concealing disclosure, impartiality disclosure, and no disclosure) in influencer marketing on influencer-related outcomes (user engagement, user sentiment, and influencer credibility) and marketer-related outcomes (user attitude towards the brand and users' intention to purchase). We conducted two field experiments and an online survey with an experimental design in collaboration with an active micro-influencer on Instagram. The results of the studies indicate that from a marketers' perspective, it is best when influencers promote products as genuine recommendations and use impartiality disclosure. From an influencer's perspective, the optimal disclosure strategy depends on whether the influencer seeks to improve engagement with their content or their levels of credibility. When influencers' primary focus is to increase engagement, if they provide information on sponsorship or non-sponsorship, they do not have to worry about decreasing engagement rates due to the employed disclosure strategy. Suppose influencers' goal is to increase their credibility. In that case, it depends on their content (whether it is rich in genuine recommendations or sponsored content) and the group they want to target—i.e., if they seek to target followers versus non-followers.
Keywords: M37; 620; Influencer marketing; Disclosure; Instagram; Follower behaviors; Field experiment